ATR‐FTIR measurements of albumin and fibrinogen adsorption: Inert versus calcium phosphate ceramics. Issue 11 (19th May 2015) - Boix, Marcel; Eslava, Salvador; Costa Machado, Gil; Gosselin, Emmanuel; Ni, Na; Saiz, Eduardo; De Coninck, Joël
Abstract Arthritis, bone fracture, bone tumors and other musculoskeletal diseases affect millions of people across the world. Nowadays, inert and bioactive ceramics are used as bone substitutes or for bone regeneration. Their bioactivity is very much dictated by the way proteins adsorb on their surface. In this work, we compared the adsorption of albumin and fibrinogen on inert and calcium phosphates ceramics (CaPs) using attenuated total reflection Fourier transform infrared spectroscopy (ATR‐FTIR) to follow in situ protein adsorption on these materials. To this effect, we developed a sol‐gel technique to control the surface chemistry of an ATR‐FTIR detector. Hydroxyapatite adsorbed more albumin and β‐tricalcium phosphate adsorbed more fibrinogen. Biphasic calcium phosphate presented the lowest adsorption among CaP for both proteins, illustrating the effect of surface heterogeneities. Inert ceramics adsorbed a lower amount of both proteins compared with bioactive ceramics. A significant change was observed in the conformation of the adsorbed protein versus the surface chemistry. Hydroxyapatite produced a larger loss of α‐helix structure on albumin and biphasic calcium phosphate reduced β‐sheet percentage on fibrinogen. Inert ceramics produced large α‐helix loss on albumin and presented weak interaction with fibrinogen. Zirconia did not adsorb albumin and titanium dioxide promoted huge denaturalization of fibrinogen. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3493–3502, 2015.